A catalogue of the Iranian Mesostigmata (Acari): additions and updates of the previous catalogue - Alireza Nemati; Elham Riahi; Arsalan Khalili-Moghadam; Dariusz J Gwiazdowicz (Persian Journal of Acarology)
The present catalogue deals with the results of a survey carried out on available literature consisted of collected and identified mesostigmatic mites associated with different kinds of host/habitats in Iran. Some family, genera, and species of mesostigmatic mites of Iran which were not included in the checklist provided by Kazemi and Rajaei, 2013 as well as their distribution data are presented. Overall, a total of 371 species out of 127 genera belonging to 39 families were listed in the present paper. Consequently, by considering Phytoseiidae family, the list of mesostigmatic mites reported from different parts of Iran was increased into 47 families, 172 genera and 620 species. It is also worth mentioning that Ololaelaps gamagarensis Jordaan & Loots was considered as junior synonym of O. mooiensis Ryke and Pseudoparasitus talebii Nemati, Malekshahkoohi & Afshari, was considered as junior synonym of P. hajiqanbari Kazemi.